EFL Pre-Service Teachers’ Use of Command Speech Acts Across Microteaching Stages - Ayu Monic Veronica; Dewi Cahyaningrum (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Command Speech acts are important for directing activity, managing the classroom, and giving instruction. While previous studies have documented command patterns among experienced teachers across educational levels, none has applied a systematic classification to pre-service teachers in microteaching, where pre-service teachers first encounter these demands. This study therefore examined the types of command speech acts produced by four EFL pre-service teachers during microteaching sessions at a state university in Surakarta, Indonesia, and how these commands were distributed across the teaching stages. A qualitative case study was conducted using video-recorded observations and two rounds of semi-structured interviews with member checking. Data were analysed following Miles et al.’s (2020) interactive model, with commands coded according to Bertsch et al. (2009) and lesson stages identified using Harmer’s (2007) ESA framework. Trustworthiness was ensured through Lincoln & Guba’s (1985) criteria. All four participants confirmed the accuracy of 382 command speech acts. Command production was strongly concentrated in question-based forms, interpreted as a pragmatic response to the peer-equality dynamic in microteaching, with regular commands accounting for most of the remainder and prohibition-type commands comparatively rare. Based on the lesson stages, most commands were produced during the Study phase, with comparatively fewer commands during the Engage (opening) and Activate (closing) phases. This suggests pre-service teachers already adjust their command choices to the demands of each stage. These findings provide an evidence-based basis for helping pre-service teachers align their choice of commands with instructional goals and classroom needs.